PEMBUATAN GAME “WOODLAND SURVIVAL” BERBASIS WINDOWS - Sandy Tanudjaja; Tony Tony; Darius Andana Haris (Fakultas Teknologi Informasi Universitas Tarumanagara, 2016)
“Woodland Survival” is a game of two combined genre: Survival and Minigames, with the goal of entertaining players of all ages. The game is produced with Unity game engine with Javascript for the programming, and Clip Studio Paint for the visual.Alpha testing of the game is done by mentors, while beta testing is done by allowing users of various ages play the game and then having them fill a questionnaire about the game. The result shows that the majority of respondents agree the game is entertaining and they are interested to play again in the future.